Telling a good one : the process of a Native American collaborative biography - Rios, Theodore (American Indian lives., 2000)
Telling a Good One is the first comprehensive examination of the collaborative process that creates a Native American life story. Kathleen Mullen Sands draws on her partnership with the late Theodore Rios, a Tohono O'odham (formerly Papago) narrator, to address crucial issues surrounding the inscribing of a life story. Sands examines the creative, critical, and cultural processes behind this increasingly popular mode of self-expression. The impetus, initial negotiations, interview process, narrative content and style, and the editing and interpretation phases of a Native American life story are all given equal scrutiny. Of particular interest are Sands's successes and failings as a collaborator and the influence of Tohono O'odham culture and its tradition of storytelling on Rios's actions and words. Sands examines the effects of her personal background and academic training on her actions and decisions, how her experiences compare with other collaborative autobiographies and biographies, and the role of academia and publishers in shaping expectations about the content and format of Native American biographies and autobiographies.